Review—Carbon Electrodes in Magnesium Sulphur Batteries: Performance Comparison of Electrodes and Future Directions. Issue 12 (30th December 2021) - Chadha, Utkarsh; Bhardwaj, Preetam; Padmanaban, Sanjeevikumar; Kabra, Dikshita; Pareek, Garima; Naik, Samriddhi; Singh, Mahika; Banavoth, Murali; Sonar, Prashant; Singh, Shalu; Latha, Srinivasan; Ray, Arun Kumar; et al.
Abstract : Magnesium-sulfur batteries have developed as a new and emerging technology benefiting from high energy density, low cost, reasonable safety, and excellent energy storage due to the high natural abundance of electrochemically active materials and low dendrite formation in magnesium. Here we report various enhancement strategies and also focus on using carbon electrodes, coating layers of carbon over the cathodes, carbon nanotubes, reduced graphene oxide, graphene-carbon nanotubes in magnesium-sulfur batteries because of its high conductivity and improved overall electrochemical functioning of the magnesium-sulfur battery. However, developing these batteries remains challenging due to significant problems caused during theirs operation, such as self-discharge, Mg-anode passivation, insufficient reversible capacity, low sulfur cathode utilization, and rapid capacity loss. We acknowledge the synthesis of non-nucleophilic electrolytes, both situ characterizations of anode or electrode reactions and kinetics, strategic development of sulfur-based cathodes and carbon electrode in Mg–S battery as a critical factor toward improvement in cycle performance, specific capacity, overpotential and working voltage, and confinement of Mg-PS polysulfide, to limit the shuttling of polysulphides, steady accumulation and desolvation of magnesium divalent ions to create a magnesium-conducting surface electrode interphase(SEI). We also present a detailed description of the Mg–S battery, its challenges, future research directions for the practical implementation of the various developed electrolyte and electrodes.